Recharge characterization by geoelectrical imaging and the GIS of the Plio-Quaternary aquifer (a case study of Central Haouz- Marrakesh) - Meriem Snineh; Khalid Mehdi; Said El Goumi; Nour-Eddine Laftouhi; Abdennabi El Mandour (European Scientific Journal, ESJ, 2020)
Groundwater resources in Morocco are increasingly scarce. The study area which is Central Haouz belonging to the Marrakech plain is not immune to this phenomenon. This is due to the semi-arid climate on the one hand, and on the other hand, due to accelerated population growth and the economic development implications. The Plio-Quaternary aquifer of the Central Haouz has been the subject of several studies, but its Hydrogeological characterization has been classically carried out using geological and pumping test studies. Our study is in this sense to show the importance of the contribution of GIS and Electrical Resistivity Tomography (ERT). The first GIS approach determined the Runoff coefficient, which helps to locate low runoff areas corresponding to recharge zones of the water table. These areas are chosen as the site for geophysical surveys. The second method consists to detect the effect of the recharge to increase the water table in the study area and the characterization of the aquifer. Four ERT surveys were performed showed on the aquifer the positive effect of the recharge dike recently built at the Wadi and dismantle the reliability of the GIS results concerning the infiltration zones founded.